Gérard Grisey, Accordionist. Issue 1 (26th April 2018) - GOLDMAN, JONATHAN
Abstract: It is tolerably well known that Gérard Grisey's first instrument was the accordion, but little has been written about the influence the pioneering spectral composer's main instrument had on his compositional language. The decade of the 1960s was marked by the centrality of the accordion and saw the completion of his first youthful compositional essays, most of which were scored for the accordion. It was also the period in which he studied at a school devoted to the accordion, in Trossingen. Later, when studying with Messiaen in Paris, Grisey distanced himself from the accordion, writing in 1969 that 'I am not playing accordion anymore. My way is another one.' After establishing the chronology of Grisey's engagement with the accordion, this article assesses the extent to which the spectral composer's training on the accordion left traces in his mature compositions and raises questions about the standard historiographies (and geographies) of French spectral music.